Replication of spodoptera litura nucleopolyhedrovirus in insect-derived cell lines - Mohd Noh, Norhalina (2014)
Spodoptera litura nucleopolyhedrovirus (SpltNPV) showed promising ability in controling Spodoptera litura outbreak and may play a unique role in the IPM system to control other permissive insect pests. The insect cell culture (in vitro) technique is the most suitable approach to be applied as it provides clean ease manipulation condition for viral gene improvement and large scale production of SpltNPV. Difficulties in the previous trials of in vitro propagation of SpltNPV were overcome by improvement in BV inoculums production and titration. Utilization of more cell lines from different host species and geographical isolates had provided more information concerning the SpltNPV host range. A successful in vitro propagation of Spodoptera litura nucleopolyhedrovirus (SpltNPV) was established in this study. This process was greatly influenced by the quality of the budded virus (BV) inoculum produced by in vivo propagation in its primary natural host, Spodoptera litura larvae. BV can be harvested either from infected larval haemolymph or homogenized larval tissue. Unfortunately, inocula prepared by both techniques were melanised due to oxidation of exposed larval haemolymph or tissues. This melanisation affected the in vitro virus-host interaction. However, the use of severe NPV-infected larvae and Grace’s Insect Medium during the virus inoculum preparation and storage successfully reduced the melanisation in the virus inoculum and allowed productive SpltNPV infection in susceptible insect cells. Meanwhile, the end point dilution titration technique proved to be the most rapid, accurate and economic method to measure the BV titre in this study. Seven cell lines (Sf9, SpIm, LD, MaBr, SD, T.ni and SpLi) were tested for their permissibility to the infection of SpltNPV. This permissibility screening was conducted through light and electron microscopic examination for cytopathological changes caused by SpltNPV infection. Productive infection was detected in the infected permissive Sf9 cells with the production of occlusion bodies (OBs). However, the other six cell lines showed an abortive infection and no OB was detected. These six cell lines were known as semipermissive to the infection of SpltNPV as the PCR of virus essential genes (ie-1, lef-2 and polh) detected the replication of SpltNPV until the tenth BV passage. An ultrastructural study further confirmed the infection in these cells. This indicated the formation of virogenic stroma and virus particles in the infected Sf9 nuclei while the other six cell lines shared some minor changes, such as vesicle formation and hypertrophied nuclei with no formation of virus particle. Serial passage study also revealed the capability of the BV progeny to effectively infect Sf9 cells with productive infection until the tenth BV passage. Apoptosis occurrence in SpIm, SpLi cells and Sf9 cells is responsible for preventing and limiting SpltNPV propagation in these cell lines. This phenomenon was detected through the cells morphological changes assessment, AO/PI analysis and DNA fragmentation assay. Meanwhile, RT-PCR was used to detect and compare an apoptotic suppressor gene (p49) expression in all three cell lines. Findings showed high expression of p49 was detected in the permissive Sf9 cells at both the first and tenth passage while low expression was detected in the SpIm and SpLi cell lines. This was evidence of p49 involvement as virus armour to manipulate and conquer the Sf9 cell line system to allow SpltNPV replication and propagation. This research had provided important information of SpltNPV host range and its susceptibility against several Lepidoptera species and geographical isolates. Subsequent research had shown an apoptosis mechanism involvement in limiting viral replication which was defeated by viral apoptotic suspressor gene (p49) in permissive Sf9 cell line.